Light-improved glucose sensing on ordered Au-Ti heterostructure - Siuzdak, Katarzyna; Döhler, Dirk; Bachmann, Julien; Karczewski, Jakub; Grochowska, Katarzyna (Optik, 2020)
Non-enzymatic electrochemical platforms sensitive towards glucose presence have attracted a worldwide attention during last decades. We report on influence of solar light onto response of gold-titanium heterostructures prepared via controllable approach. The material based on Au nanoparticles orderly distributed over the structured titanium foil was obtained by electrochemical anodization followed by chemical etching, magnetron sputtering of gold and finally thermal treatment in the continuous regime. It is proven that the applied synthesis route leads to the enhanced visible light absorption boosting material photoactivity. Fabricated electrode immersed in the glucose containing solution and exposed to the solar light exhibits superior increase of oxidation current comparing to pristine substrate before thermal annealing. Photosensor is characterized by broad linear response up to 40 mM of glucose, limit of detection of 0.2 and 0.1 mM and sensitivity of 3.08 and 0.92 μA/cm2 in NaOH and PBS, respectively. It is concluded that the electrode exhibits enhanced performance taking advantage from plasmon resonance effect and the presence of thin titania passive film. Moreover, obtained material is stable under prolonged illumination and was verified in the presence of blood serum sample. Overall, presented results suggest that the impact of solar light should be taken into account during works on sensing devices.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Au-Ti heterostructure; Glucose sensing; Light enhancement; Photoactivity; Surface plasmon resonance